Agentic Architecture: A Foundation for Transforming Pharma Business Cases - Walia, Anuradha; Shinde, Amol Ashokrao (Journal of Research in Science and Engineering, 2025)
In recent years, the pharmaceutical industry has been undergoing a seismic shift, driven largely by advancements in technology. Among these advancements, generative AI stands out as a transformative force, promising to revolutionize drug discovery, enhance clinical trial efficiency, and streamline operational workflows. This white paper presents an in - depth exploration of how generative AI can be integrated into the enterprise architecture of pharmaceutical organizations. By leveraging its capabilities, companies can unlock new realms of innovation, operational efficiency, and improved patient outcomes. At the core of this transformation is the concept of Agentic Architecture - a framework that enables systems, such as generative AI, to operate with greater autonomy while remaining tightly integrated within the broader organizational ecosystem. Agentic Architecture is designed to enhance decision - making, drive innovation, and facilitate collaboration between various stakeholders, such as researchers, clinicians, and operational teams.